2011
DOI: 10.5402/2011/363578
|View full text |Cite
|
Sign up to set email alerts
|

Are Panoramic Radiographs Reliable to Diagnose Mild Alveolar Bone Resorption?

Abstract: It is extremely important to assess variations between the most used radiographs in dental practice, since minimum distortion on obtained images may change diagnosis, treatment plan, and prognosis for the patient. For this, the distance between the enamel-cementum junction and the alveolar bone crest was measured on conventional and digitized periapical, bitewing, and panoramic radiographs and compared among them. From a total of 1484 records, 39 sets of radiographs that fulfilled the inclusion criteria of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Based on studies of Li, Gomes and Faghihi that concluded that digital radiography is more accurate than plain film in assessment of periodontal bone loss (13)(14)(15) and Rebesco, Semenoff and Chitsazi that stated periapical is better than panoramic images (16)(17)(18), the results of this study can be supported by this reality that periapical images is better in detail evaluation, but with image enhancement of panoramic images, the difference can be reduced. On the other hand, in recent years, digital radiography machines have notably advanced such as larger focal trough size that causes better quality in anterior regions (4).…”
Section: Discussionsupporting
confidence: 76%
“…Based on studies of Li, Gomes and Faghihi that concluded that digital radiography is more accurate than plain film in assessment of periodontal bone loss (13)(14)(15) and Rebesco, Semenoff and Chitsazi that stated periapical is better than panoramic images (16)(17)(18), the results of this study can be supported by this reality that periapical images is better in detail evaluation, but with image enhancement of panoramic images, the difference can be reduced. On the other hand, in recent years, digital radiography machines have notably advanced such as larger focal trough size that causes better quality in anterior regions (4).…”
Section: Discussionsupporting
confidence: 76%
“…Comparison among them showed that a small reduction in height of the interseptal bone crest observed in panoramic radiographs should be carefully evaluated for overestimation. Moreover, several studies proposed that panoramic radiography might serve as a diagnostic aid in dental health evaluation programs [57].…”
Section: Patterns and Trends Of Alveolar Bone Lossmentioning
confidence: 99%
“…9,10 CBCT has great value in that it is more accurate 11,12 for assessing bony architecture or quantifying bone volume than traditional radiographic images such as periapical or panoramic views. [13][14][15][16] To our knowledge, no study has scientifically assessed the alveolar bone status of normal occlusion samples with no noticeable periodontal disease, and few studies have reported that certain malocclusion groups had greater bone loss around specific teeth than was seen in normal occlusion samples. 5 Therefore, the purpose of this study was to compare the amount of alveolar bone loss and thickness around incisors of Korean normal occlusion samples and adult skeletal Class III patients with the use of 3D CBCT images.…”
Section: Introductionmentioning
confidence: 99%